Narratives and representations of suffering, failure, and martyrdom. Early modern catholicism confronting the adversities of history - Cohen, Leonardo (2021)
This volume is the result of a colloquium organized by the Center for the Study of Religious History (CEHR) of the Catholic University of Portugal in Lisbon, titled Narratives of Suffering and Disappointment in the Early Modern Period: Giving Birth to New Martyrs in April 2015. The volume addresses the diversity of historical perspectives on the experience of disappointment and the exaltation of suffering and martyrdom in the early modern age in Asia, Africa, America, and Europe.